Developing Students' Vocabulary through Watching English Cartoon Films at SMP BHAKTI - Christopley, Christopley (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2017)
AbstractThis was a research report on developing students’ vocabulary through watching English cartoon films. The objectives of this research were to develop students’ vocabulary and students’ responses on learning vocabulary through watching English cartoon film at SMP BHAKTI, Jakarta. This research used classroom action research (CAR) method in which the students consisted of 23 eighth graders of SMP BHAKTI, Jakarta and comprised15 males and 8 females. To collect the data the researcher used test and non-test techniques. The test technique was realized in pre-test and post-test; while the non-test one was in questionnaire, observation sheet, and diary notes. Based on the test analysis results, it was found that the mean score of the pretest, post-test in Cycle 1 and 2 were 60.73 points, 80.86 points, and 90.00 points respectively. The gain between the post-test and pre-test scores in Cycle 1 was 33.14% and the gain between the post-test in Cycle 1 and post-test scores in Cycle 2 was 11.30%. The gain between pre-test and post-test scores in Cycle 2 was 48.69%. Therefore, it can be concluded that watching English cartoon films could develop the eighth graders’ vocabulary of SMP BHAKTI, Jakarta. Besides, based on the questionnaire, observation sheet, and diary notes analysis results, it was revealed that students agreed that watching English cartoon films was a good strategy to develop their vocabulary. The conclusion is that watching English cartoon films can develop students’ vocabulary.Keywords: English cartoon films, vocabulary, action research